Konsep Ketuhanan dalam Perspektif Al-Baidhawi - Furqan Furqan (Sinthop, 2023)
This article aims to understand the concept of divinity in Al-Baidhawi's interpretation, analyze its distinctive characteristics and methodology, and explore its impact on the religious life of Muslims. The method used is philosophical and historical factual, prioritizing a hermeneutical approach to interpret Al-Baidhawi's work in its original context. The research findings indicate that Al-Baidhawi, in his work "Anwar Al-Tanzil wa Asrar Al-Ta’wil", employs an analytical approach and combines the bi al-Ma’thūr and bi al-Ra’yi methods of interpretation. His interpretation encompasses linguistic, hadith, philosophical, and Sufi aspects, providing a comprehensive view of the attributes of Allah and the relationship between humans and the Creator. Al-Baidhawi considers the concept of divinity as the foundation for all religious sciences, emphasizing the importance of interpretation in understanding the Qur'an. His interpretation also demonstrates a balance between intellectual and spiritual dimensions, guiding Muslims to experience the presence of Allah in all aspects of life. This study concludes that Al-Baidhawi's interpretation offers a significant contribution to the understanding of the concept of divinity, not limited to theoretical aspects but also practical, directing Muslims to lead a life enlightened by faith and devotion to Allah.